2015
DOI: 10.1111/add.12947
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine‐related stimuli impair inhibitory control in cocaine users following short stimulus onset asynchronies

Abstract: Background and Aims Cocaine users display a significant increase in inhibitory failures following cocaine-related images compared with neutral images in a modified cued go/no-go task, the Attentional Bias-Behavioral Activation (ABBA) task. The aim of this study was to demonstrate that stimulus onset asynchrony (SOA) impacts inhibitory failures on the ABBA task. Design A between-subjects experiment. Setting An outpatient research unit in the USA. Participants Ninety-one cocaine users recruited from the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In two studies, use of tasks with this type of stimuli was associated with worse inhibition performance in CU, detected as a greater variability in RT 35 and increased inhibition deficits in responses. 37 In contrast, another study using a similar task did not detect this association. 48 It is therefore important to understand the possible dysfunctions related to information processing exhibited by CU, such as attentional bias for cocaine and/or crack, for example, since such findings could contribute to treatment, to prevention of relapses, and to cognitive rehabilitation of these people.…”
Section: Discussionmentioning
confidence: 90%
“…In two studies, use of tasks with this type of stimuli was associated with worse inhibition performance in CU, detected as a greater variability in RT 35 and increased inhibition deficits in responses. 37 In contrast, another study using a similar task did not detect this association. 48 It is therefore important to understand the possible dysfunctions related to information processing exhibited by CU, such as attentional bias for cocaine and/or crack, for example, since such findings could contribute to treatment, to prevention of relapses, and to cognitive rehabilitation of these people.…”
Section: Discussionmentioning
confidence: 90%
“…This outcome is consistent with epidemiological findings in that nearly half of individuals who met criteria for cocaine dependence also met criteria for comorbid alcohol dependence in the US (United States Department of Health and Human Services, 2016). Cocaine users displayed impaired inhibitory control following cocaine cues (Pike et al, 2013, 2015). Alcohol impairs inhibitory control in drinkers (e.g., Dougherty et al, 1999; Marczinski and Fillmore, 2003, 2005; Weafer and Fillmore, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ABBA task is a modified Cued Go/No-Go reaction time task, which was administered using E-prime experiment generation software (Psychology Software Tools, Pittsburgh, PA) on a PC computer (described in detail Pike et al, 2013, 2015; Weafer and Fillmore, 2012). The task consists of 250 trials divided into 5 blocks of 50 trials (sample trials are shown in Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations